SOME ASPECTS OF STEAM-WATER FLOW CRITICAL STAGE IN THE DEVELOPMENT OF GEOTHERMAL FIELDS - Shulyupin A.N. (My University, 1996)
The critical stage of steam-water flow is considered as a condition for the theorem of momentum being independent of pressure gradient. A mechanism is proposed for the effect of a local critical stage influencing the flow structure. Several models are tested to obtain analytical relations for the flow velocity. Critical stages can arise in local flows that move at velocities common for two-phase flows in geothermal fields. Local supercritical flows can exist at the vents of steam-water discharge. This affects the behavior of the upward flow; the actual velocities averaged over the cross-section may exceed the calculated values.